Development of MRI-defined Structural Tissue Damage after Anterior Cruciate Ligament Injury over 5 Years: The KANON Study. - Roemer, Frank; Lohmander, L. Stefan; Englund, Martin; Guermazi, Ali; Akesson, Anna; Frobell, Richard (Radiology, 2021)
Background MRI is used to evaluate structural joint changes after anterior cruciate ligament (ACL) injury, but no long-term data are available for comparing different treatment approaches. Purpose To describe structural joint damage with MRI over a 5-year period in the Knee Anterior Cruciate Ligament, Nonsurgical versus Surgical Treatment (KANON) study and to compare frequencies of such tissue damage for a nonsurgical versus a surgical treatment strategy. Materials and Methods In this secondary analysis of a prospective trial (ISRCTN 84752559), 119 participants with an acute ACL injury were evaluated. Participants were enrolled from 2002 through 2006, the 2-year follow-up started in 2008, and the 5-year follow-up started in 2011. A 1.5-T MRI examination was performed at baseline and at 2- and 5-year follow-up. MRI scans were read according to a validated scoring instrument. Kruskal-Wallis tests were used to assess whether the frequencies of structural damage differed between the three as-treated groups. Results Of 119 participants (mean age, 26 years ± 5 [standard deviation]), 91 men were evaluated. At 2- and 5-year follow-up, respectively, 13% (15 of 117) and 13% (15 of 115) of knees showed incident cartilage damage in the medial tibiofemoral joint, 11% (13 of 117) and 17% (20 of 115) of knees showed incident cartilage damage in the lateral tibiofemoral joint, and 4% (five of 117) and 8% (nine of 115) of knees showed incident cartilage damage in the patellofemoral joint. Osteophyte development was seen in 23% (27 of 117) and 29% (33 of 115) of knees in the medial tibiofemoral joint, in 36% (42 of 117) and 43% (49 of 115) of knees in the lateral tibiofemoral joint, and in 35% (41 of 117) and 37% (42 of 115) of knees in the patellofemoral joint. No major differences between the groups were found for incident or worsening cartilage damage, bone marrow lesions, and osteophytes at 2 or 5 years. The rehabilitation-alone group showed less Hoffa-synovitis at 2 (P = .02) and 5 (P = .008) years. Conclusion Young adults with anterior cruciate ligament injury showed no major difference in frequency of structural tissue damage on MRI scans at 2 and 5 years regardless of treatment. However, the rehabilitation-alone group had less inflammation at 2 and 5 years. © RSNA, 2021 Online supplemental material is available for this article. See also the editorial by Andreisek in this issue.
EVALuna2:487331